Can whale-watching and whaling co-exist? Tourist perceptions in Iceland. (4th March 2014) - Bertulli, Chiara G.; Leeney, Ruth H.; Barreau, Thomas; Matassa, Danilo Swann
Abstract : Both whaling and whale-watching tourism occur in Iceland, but these activities are considered incompatible by many, and previous studies have suggested that whale-watch tourists would boycott whale-watch destinations where whaling takes place. This study assessed the perceptions of and attitudes towards ongoing whaling amongst whale-watch tourists in Iceland. A majority of whale-watching tourists in Iceland did not support whaling and did not think that whale-watching and whaling could exist side by side. However, 31% of respondents were unaware of Iceland's whaling before their visit and most of these indicated that prior knowledge of whaling activities would not have affected their choice of destination. More tourists had tried whale meat than either puffin or guillemot meat, suggesting that whale meat may be more strongly marketed to tourists visiting Iceland. These results suggest that not all tourists would consider boycotting travel to a whaling nation. The whale-watch industry is important to Iceland's economy, but given that the whaling industry can potentially negatively impact upon whale-watching activities, a careful analysis of the compatibility of these two industries is recommended.